EFFICACY AND SAFETY OF PHARMACOLOGICAL TREATMENT OF THE WITH CLINICALLY APPARENT BACTERIURIA AND ASYMPTOMATIC BACTERIURIA IN THE PREGNANT WOMEN - Dmitry Likhikh; Galina Lazareva (Belgorod National Research University, 2017)
The article explores the problem of urinary tract infection in pregnant women. It presents the statistical analysis of the frequency of different forms of urinary tract infection during pregnancy. Our data is compared to the statistics given by other national and international researchers. This research makes an attempt to compare two different treatment methods: using cefixime in dose 400mg 1 per day for 7 days and amoxicillin/clavulanate in dose 625mg 3 per day for 7 days. During the research conducted from September 2009 until June 2012 at State Healthcare Institution "Regional perinatal centre", 984 patients in I, II and III pregnancy trimesters were studied. In order to find out a potential influence of urinary tract microflora character for the intrauterine development, as well, as presence of infectious inflammatory diseases in neonates, a clinical observation of neonatal period for all the children born from the studied mothers was conducted. A special attention was directed to appearance of different clinical infection forms. We find out that the pregnant women with the asymptomatic bacteriuria should be administered the antibiotics treatment in order to prevent clinically apparent urinary tract infections, to stop uropathogen flora growth and to limit their affect on fetus development. Microbiological urine testing for the patients in the course of the urinary tract infection may be employed as an informative test for evaluating the antibiotics treatment efficacy. Given a positive effect Amoxicilline/Clavulanate and Cefixime treatment may be recommended to the pregnant women with clinically apparent UTI and with asymptomatic bacteriuria.